The 23rd Digital Avionics Systems Conference (IEEE Cat. No.04CH37576)
DOI: 10.1109/dasc.2004.1391263
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of terminal RNAV mixed equipage

Abstract: Airlines continue to acquire or equip existing aircraft with improved and more capable avionics. Improvements such as the Flight Management System (FMS) allow aircraft to fly preplanned paths with precision. Attempts to take advantage of improved aircraft guidance to make approaches, amvals, and departures in the terminal area more uniform and predictable are consequently a natural development in air traffic control. The use of Area Navigation (RNAV) routes is one example of exploiting the current avionics tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The availability of RNAV routes may reduce ATCO workload by (a) reducing communication time with the pilot and (b) reducing the need to monitor conformance of aircrafts, thereby reducing the cognitive load caused by the monitoring task. Research using RNAV operations has reported a reduction in ATCO communication workload (Barker, Haltli, MacWilliams, & McKee, 2003;Sprong, Haltli, DeArmon, & Bradley, 2005) and a change in SA with increased traffic levels (Smith, 2007). Future research should further assess workload and SA (as well as issues of ATCO stress, trust, and boredom) under RNAV conditions to ensure the safety and efficiency of future systems.…”
Section: Future Atm Systemsmentioning
confidence: 98%
“…The availability of RNAV routes may reduce ATCO workload by (a) reducing communication time with the pilot and (b) reducing the need to monitor conformance of aircrafts, thereby reducing the cognitive load caused by the monitoring task. Research using RNAV operations has reported a reduction in ATCO communication workload (Barker, Haltli, MacWilliams, & McKee, 2003;Sprong, Haltli, DeArmon, & Bradley, 2005) and a change in SA with increased traffic levels (Smith, 2007). Future research should further assess workload and SA (as well as issues of ATCO stress, trust, and boredom) under RNAV conditions to ensure the safety and efficiency of future systems.…”
Section: Future Atm Systemsmentioning
confidence: 98%
“…In addition, the findings indicated that an explanation as to how RNAV had reduced flight time variation, lateral dispersion, airspace usage and inter-arrival times. Barker et al (2004) reported on issues associated with mixing of aircraft that were RNAV equipped with non-RNAV equipped aircraft. The simulation analysis confirms that there are benefits using RNAV equipage in TMA for arrivals.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Most previous studies related to the PM system have focused on providing a reduction in the total number of controller instructions, frequency occupancy time as well as fuel consumption and environmental impact by enabling Continuous Descent Approaches (CDA) (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) , which allow aircraft to descend continuously by employing minimum engine thrust, ideally in low drag configuration, prior to the final approach fix/final approach point (31) . LH has been applied in Dublin since 2012.…”
Section: Introductionmentioning
confidence: 99%